NEW TOYS, NEW APPS, NEW IDOLS: K-POP'S AI IMAGINARY - Keith, Sarah (Brazilian Creative Industries Journal, 2024)
This article explores how AI is imagined in processes of cultural production, using K-pop as a case study. K-pop serves as a ‘canary in the coalmine’ for the global music industries, having adapted to technological change earlier than its regional counterparts. In this article, I examine the perspectives of K-pop management companies, fans, and the IT sector in depicting AI as a future-making technology. It explores how K-pop stakeholders envision AI's transformative effect on the creative and cultural industries, highlighting differences in their AI imaginaries and visions of AI's utility. Stakeholders reveal different and contrasting perspectives, shedding light on the future of the industry and the broader creative culture sector. These imaginaries of AI reveal how AI exists within networks of power and capital, and indicate different visions of AI as a future-making technology in the music industry. The discussion calls for further critical analysis of AI as a socially constructed concept, and its implications for the future of music.